Sponsorship of the Tokyo 2020 Olympic Games and the FIFA World Cup Qatar 2022 on X and Instagram: A comparative analysis of digital activation and content type - Sanahuja Peris, Guillermo; Fernández Peña, Emilio; Mut Camacho, Magdalena (Revista Latina de Comunicación Social, 2025)
Introduction: The aim of this study was to perform a comparative analysis of the activation of sponsorship of the Tokyo 2020 Olympic Games and FIFA World Cup Qatar 2022 on social media. Methodology: A mixed-method study design was conceived, combining an analysis of the quantitative and qualitative content of posts on the global and Spanish X and Instagram accounts of 16 sponsors. These were International Olympic Committee and Spanish Olympic Committee sponsors, as well as official FIFA World Cup 2022 sponsors. Results: After analysing a sample of 4,791 posts, the results revealed interesting findings regarding the volume of posts about these two mega-events on the one hand, and the thematic types of post on the other. In general terms, it was concluded that the Olympic sponsors had devoted efforts to promoting their links with the Olympic Games, while the FIFA World Cup sponsors had generated a higher number of posts. At the same time, it was found that cross-pollination had only been partially used in the brands’ stories: some did not interconnect their global and national communication strategies, and the brands’ stories on X and Instagram did not match. Conclusions: The most common themes of the activation of both sponsorships were informing and interacting, which stood out much more than other types such as entertaining or rewarding.